Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/app11146411
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Restoration of Tributyltin Contaminated Environments Using Marine Bacteria from Portuguese Fishing Ports

Abstract: Tributyltin (TBT) is an organotin chemical mainly used as biocide in marine antifouling paints. Despite the restrictions and prohibitions on its use, TBT is still an environmental problem due to its extensive application and subsequent release into the environment, being regarded as one of the most toxic chemicals released into the marine ecosystems. Microorganisms inhabiting impacted sites are crucial for their restoration since they have developed mechanisms to tolerate and break down pollutants. Nonetheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The TBT-resistant culture isolation growth behavior represents the toxicity reduction methods into sublethal levels. Strikingly, the potential of these bacteria as bioremediation agents was evaluated through microbiological assays using the Pseudomonas species as model organism [33,35,36]. Kinetics modeling of TBT toxicity on the growth of Bacillus stearothermophilus was studied in a recent report [37].…”
Section: Resultsmentioning
confidence: 99%
“…The TBT-resistant culture isolation growth behavior represents the toxicity reduction methods into sublethal levels. Strikingly, the potential of these bacteria as bioremediation agents was evaluated through microbiological assays using the Pseudomonas species as model organism [33,35,36]. Kinetics modeling of TBT toxicity on the growth of Bacillus stearothermophilus was studied in a recent report [37].…”
Section: Resultsmentioning
confidence: 99%
“…The tolerance mechanisms developed by microorganisms that inhabit the impacted sites could be exploited in remediation processes, for example in [12], where it is reported that marine bacteria collected from seven Portuguese fishing ports were isolated and grown in the presence of Tributyltin (TBT). The bacteria that exhibited higher growth were evaluated for their capability to degrade this highly toxic, endocrine disrupting compound.…”
mentioning
confidence: 99%